Implementation of CSP1 Matrix Application for Roof Defects Monitoring : Case Study in F2 Examination Hall UTHM - Zahri, Mohamad Ridhwan; Suhandri, Hendy Fitrian (Recent Trends in Civil Engineering and Built Environment, 2024)
The roof is a component of the structure's covering and usually it’s place in a higher place that need to use ladder to see the condition. Furthermore, because of the risks posed by these characteristics, roof inspectors have difficulties completing rooftop inspections owing to the high roof structure and assisting it if it runs on it. The goal of this research is to use a UAV to enter faulty structures for visual inspection and to categories roof building problems using the CSP1 Matrix as a technique of evaluation and ultimately acquire the condition of the roof condition between the main hall of Universiti Tun Hussein Onn Malaysia. The main hall was elected in the UTHM area namely the examination hall (F2) UTHM. Unmanned Ariel Vehicles (UAV) was used for visual monitoring and Condition Review Protocol (CSP) 1 Matrix was used to analyze the assessment of building roof conditions and to identify the seriousness of defective buildings detected for the roof’s hall. Therefore, 19 defects for F2 examination hall UTHM have been recorded on the roof surface and the overall roof condition is calculated is 2.4 (Green). The result indicates that the state of the roof for F2 examination hall UTHM is in a fair condition (score 1-4) by referred to overall roof rating by CSP1 Matrix. Total defects in research studies are 46.